Remote Sensing Techniques for Evaluating Land Use/Land Cover: a Case Study - Gupta, H. S. (Indian Forester, 2001)
The present study depicts that the satellite remote sensing data can be of great help in quick assessment and real time monitoring of existing natura] resource, like water and forest and it can be effectively used for catchment area evaluation, change pattern in command area etc. The integration of various database through GIS provides insight into verifying the details of Water resources or other projects submitted under the provisions of Forest (Conservation) Act. The present study provides the baseline spatial database for forest manager to quickly asses evaluate and monitor the change in forest resources/Environment under the impact of the dam, any time in future also.